Legal Conflict in Isbat Nikah of Polygamous: Perspective of SEMA Number 3 Year 2018 and its Implications for Biological Justice - Achmad Sofyan Aji Sudrajad; Ibrahim Siregar; Zul Anwar Ajim Harahap (Tribakti: Jurnal Pemikiran Keislaman, 2024)
This article examines the legal conflicts associated with marriage validation (isbat nikah) in the context of polygamous marriages, particularly in relation to the Supreme Court Circular Letter (SEMA) No. 3/2018 and its implications for biological justice. SEMA No. 3/2018 mandates the rejection of isbat nikah applications based on informal or unregistered marriages to uphold legal certainty. The study employs normative research methods, incorporating conceptual, statutory, case, and comparative approaches. The conceptual approach is utilized to explore theories of biological and procedural justice. The statutory approach analyzes relevant legal provisions, with a focus on SEMA No. 3/2018 and marriage law. The case approach provides an in-depth analysis of two pivotal court decisions: the Cilacap Religious Court Decision No. 0430/Pdt.P/2019/PA.Clp and the Supreme Court Decision No. 223/K/Ag/2020. The comparative approach evaluates how these cases illustrate differing applications of the law. Data are analyzed qualitatively and descriptively to uncover and understand disparities in the application of justice. The study critically assesses the implications of SEMA No. 3/2018 on biological justice, highlighting the need for not only legal recognition of marriages but also robust protection of all parties' rights. The findings reveal significant deficiencies in the current legal framework, advocating for a more nuanced approach that reconciles legal recognition with the protection of biological rights. The research offers comprehensive recommendations for policymakers and legal practitioners aimed at enhancing legal provisions for individuals in unregistered polygamous marriages. These recommendations emphasize the importance of fostering dialogue among legal experts and updating regulations to ensure both procedural and substantive justice. Theoretical implications suggest that procedural and biological justice may conflict in the realm of isbat nikah in polygamous marriages, necessitating a more integrated and holistic legal approach to achieve substantive justice for all involved parties.